2017
DOI: 10.1093/molehr/gax071
|View full text |Cite
|
Sign up to set email alerts
|

Raman micro-spectroscopy analysis of different sperm regions: a species comparison

Abstract: This work was supported by BMBF project 'Sperm Ident' (FKZ:13N13024) and the DAAD-CRUP bilateral exchange program (AI A06/16-57213087). S.A. is a recipient of a fellowship from the Portuguese foundation for science and technology (FCT-SFRH/BPD/110160/2015) and R.DC. is a recipient of a DAAD PhD stipend (91590556). There is no competing interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…The mean spectrum of each treatment was obtained and peak assignment was done having as reference the works of Talari et al [ 29 ] and Amaral et al . [ 26 ] which we highly recommend for further details about the spectral profile of sperm cells. The measurements of all individual spectra (over the 650–1,800 cm-1 spectral range) were analyzed by Standard principal component analysis (PCA) and plotted using the R 3.4.1 and RStudio 1.0.153 [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean spectrum of each treatment was obtained and peak assignment was done having as reference the works of Talari et al [ 29 ] and Amaral et al . [ 26 ] which we highly recommend for further details about the spectral profile of sperm cells. The measurements of all individual spectra (over the 650–1,800 cm-1 spectral range) were analyzed by Standard principal component analysis (PCA) and plotted using the R 3.4.1 and RStudio 1.0.153 [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This technique has also been applied for the non-invasive sex assessment in bovine semen, being able to distinguish X and Y bearing sperm [ 24 , 25 ]. Recently our group reported that several organelle-specific (sperm head, midpiece and tail) spectral features are present in human, monkey, mouse and sea urchin sperm, which could be considered potential spectral markers for sperm quality [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has so far presented controversial data on sperm evaluation, and except for nuclear DNA, the identification and assignment of spectral bands in Raman-profiles to the different sperm regions remains to be established ( Amaral et al ., 2018 ). Raman microspectroscopy is a promising tool in the assessment of male fertility, but studies are, unfortunately, in their infancy, which may delay its potential use in IVF.…”
Section: Resultsmentioning
confidence: 99%
“…To establish a new diagnostic technique based on the Raman spectroscopy that is able to distinguish between sperm with normal and abnormal chromatin condensation it is essential to understand the Raman spectra of the sperm components and Raman spectral differences between normal sperm and sperm with chromatin condensation abnormalities. Previous studies analyzed Raman spectra and correlated spectral features to various properties [25,26,[39][40][41][42][45][46][47][48][49][50][51][52]. The presence of the Raman peak around 670 cm -1 represents the ring breathing mode of guanine, indicates that the DNA backbone was in B-form conformation [53].…”
Section: Discussionmentioning
confidence: 99%